Symptom management in patients with cancer of the female reproductive system receiving chemotherapy - Phianmongkhol Y. (2014)
This study was conducted to examine the feelings, symptom management, and needs of patients with gynecological cancer receiving chemotherapy at Chiang Mai University Hospital, Chiang Mai, Thailand. During the period July 2006 and June 2007, 286 patients were recruited. The most common chemotherapeutic regimen was paclitaxel and carboplatin followed by single carboplatin and weekly cisplatin. Five severe and frequent complications were as follows: alopecia, anorexia, fatigue, nausea, and vomiting. Some 41.9% could well tolerate with such complications but 50.3% had various feelings including irritability, boredom, dejection, fear, stress, and anxiety. Anorexia was the symptom that the majority of them could best manage, 17.4% by eating as much as they can and 32.6% by selecting different foods from normal, such as fruit, sweetmeats, noodles, milk. For nausea and vomiting, 31.3% managed by eating fruit, drinking sour juice, and holding sour fruit in mouth, and 16.0% used the breathing method, eating something cold, such as ice-cream, or hot food like noodles. For health needs, 41.0% needed encouragement, care, health education, and information from doctors and nurses, and 5.0% needed care and encouragement from their family, and sympathy from neighbors and colleagues. In conclusion, gynecological cancer patients receiving chemotherapy experience a variety of feelings, symptom management. and health needs. Nurses need to explain the pathology of the occurring symptoms so that the patients can understand and accept the symptoms to lessen their negative impact.